2022
DOI: 10.18203/2394-6040.ijcmph20220003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, etiology, and treatment of denture stomatitis

Abstract: Multiple factors are involved in the pathogenesis of denture stomatitis, which increases the risk of tissue infection and inflammation. These factors include poor oral hygiene, trauma secondary to poorly fitting prostheses, resin porosity, and bacterial plaque accumulation. Our present review discusses the epidemiology, etiology, and treatment of denture stomatitis based on data from current studies in the literature. The prevalence of denture stomatitis is significantly variable among the different studies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Meticulous oral hygiene, including prosthesis care, is important in achieving the resolution of DS [ 55 ]. Riberio et al [ 2 ] proposed a hygiene protocol that has shown to be effective in reducing the inflammation associated with DS and involves the following: Brushing the hard palate for 2 min, three times a day with soft toothbrush bristles and water; During the day, brush the dentures for 2 min, three times a day, with a denture brush and neutral, non-abrasive liquid soap; Before going to bed at night, soak the dentures in 150 mL of 0.25–0.5% sodium hypochlorite for 10–20 min, followed by the overnight storage of the dentures in fresh, clean water at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Meticulous oral hygiene, including prosthesis care, is important in achieving the resolution of DS [ 55 ]. Riberio et al [ 2 ] proposed a hygiene protocol that has shown to be effective in reducing the inflammation associated with DS and involves the following: Brushing the hard palate for 2 min, three times a day with soft toothbrush bristles and water; During the day, brush the dentures for 2 min, three times a day, with a denture brush and neutral, non-abrasive liquid soap; Before going to bed at night, soak the dentures in 150 mL of 0.25–0.5% sodium hypochlorite for 10–20 min, followed by the overnight storage of the dentures in fresh, clean water at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The development of DS can be attributed to various etiological factors, one of which is the presence of biofilm on the surface of the denture [ 2 ]. This biofilm is a complex mixture of pathogenic and opportunistic microorganisms, such as bacteria, fungi, desquamated epithelial cells, and biofilm matrix.…”
Section: Introductionmentioning
confidence: 99%